Re-Appraising the Benefits of French Language Education in Nigeria for Job Creation, Peace, Stability and Sustainable Development - Ogilo , Mary (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
One of the primary objectives of education in Nigeria is to ensure the acquisition of appropriate skills and the development of mental, physical and social abilities and competences as tools for the individual to contribute meaningfully towards societal development. French language education is one of such educational subject that can guarantee the attainment of this goal. This paper therefore sought to show how French language can be an instrument for job creation. It examined the concept of French language education, looked at the place of French language education in National Development. It also examined the role of French language education in promoting peace, security and regional integration as well as scientific and technological development. It looked at the role of French language education in job creation and the economic growth of the nation. It ended by proffering some suggestions before concluding. The paper shows that if French language is given the attention it deserves, Nigeria will take her place as the giant of Africa and contribute meaningfully in the world affairs. This paper serves as an awakening call to government at all levels in Nigeria from Local, State to Federal to formulate policies and programmes and implement them.